Use of Streptococcus Salivarius K12 in a cohort of PFAPA patients - Spagnolo, Alessandra; Mileto, Vincenzo; Civino, Adele; Maggio, Maria Cristina; Risso, Paolo; Sestito, Simona; Gallizzi, Romina (Frontiers in Pediatrics, 2024)
Background Periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis syndrome (PFAPA) is the most common cause of periodic fever in childhood. Although PFAPA is generally a self-limited condition, it can have negative impact on child's and parents’ quality of life and family functioning. Our primary aim was to assess the potential effectiveness of Streptococcus Salivarius K12 (SSK12) in preventing febrile attacks in PFAPA patients. Secondary objectives included evaluating the effectiveness of SSK12 in mitigating the severity of febrile episodes seen as a statistically significant reduction in the episode duration, highest fever temperature reached during fever, in the frequency of each associated symptom, calculated in the six months before and after the start of therapy. Results A total of 117 patients with PFAPA were evaluated using Marshall's criteria, modified by Thomas et al. and according to Eurofever/PRINTO classification criteria, aged 6 months to 9 years, with a median age at the onset of the disease of 2 years, treated with SSK12, since January 2021 to January 2023. Data were collected retrospectively. Before using SS K12, febrile episodes recurred on average every 26.1 ± 11.5 days, with a febrile episode duration of 4.1 ± 1.4 days. The highest fever temperature during the episode was 39.8 ± 0.7 °C. After six months of SS K12, febrile episodes recurred on average every 70 ± 53,1 days (p value <0.01), the mean lenght of febrile episodes was 3.3 ± 1.6 (p value <0.01) and the highest fever temperature reached during the febrile episode was 39.1 ± 1.1 °C (p value <0.01). We also documented a reduction in the frequency of exudative pharyngotonsillitis present in 72 vs. 103 patients (p value <0.01), oral aphthosis present in 47 vs. 80 patients (p value <0.01), lateral cervical lymphadenopathy in 45 vs. 83 (p value <0.01). Erythematous pharyngotonsillitis decreased in frequency but it was not statistically significant. Conclusions The results of our study indicate that the use of SS K12 could be beneficial in decreasing febrile episodes related to PFAPA syndrome and its associated symptoms, potentially improving the quality of life in pediatric patients and decreasing the need for additional pharmacological therapies.